Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
JIFAM, Vol.2, Supplement 1, December 2020Life Cycle Cost Structure of a Government Office Green Building – Case of the Ministry of Public Works and Housing Main BuildingDomenico Adi Nugroho, Hitapriya Suprayitno, Tri Joko Wahyu AdiEffect of Waste Tire Rubber on the Durability Behavior of Cement Composites: A ReviewIsyaka Abdulkadir, Bashar S. MohammedPreliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset ManagementRia Asih Soemitro, Hitapriya SuprayitnoComparing the Result of Infrastructure and Facility Demand Distribution Similarity Test Between Using Percentage Value and Real ValueHitapriya Suprayitno, Vita Ratnasari, Ria Asih Aryani SoemitroLearn Asset Management based on PTPN 9 Case – Preliminary Overview of the Institution, the Function, and the General Business AssetsSoedarmawan Soewardi, Hitapriya Suprayitno, Ria Asih Aryani Soemitro JIFAM, Vol.2, Issue 2, Sebtember 2020Preliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset Management Ria Asih Aryani Soemitro &Hitapriya SuprayitnoManagement Model of Mambal Irrigation Area in the Efforts to Develop Environment-Based Agro-tourismI Gusti Agung Putu Eryani, A.A. Sg. Dewi Rahadiani & Cok Agung YujanaBase Influence Factors for Community-Based Road Quality in Slum Settlement AreasMochammad Reyhan Firland, Hitapriya Suprayitno, Eko Budi Santoso & Tri Joko Wahyu AdiAreas Evaluation of Pump Capacity in Pancasila Pumping Station, Madiun City, East Java Novi Andriany Teguh, Umboro Lasminto, Anak Agung Ngurah Satria Damarnegara & Mohamad Bagus AnsoriPreliminary Research on Air Passenger Volume Variation in Kilimanjaro International Airport, TanzaniaFreddy David Chilongola, Hitapriya Suprayitno & DewantiAnalysis of Project Performance Criteria for Design and Build Contract Taurista Yuristanti, I Putu Artama Wiguna & Herry Budianto Journal of Infrastructure & Facility Asset ManagementVolume 3, Issue 1, March 2021 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.2, Supplement 1, December 2020Life Cycle Cost Structure of a Government Office Green Building – Case of the Ministry of Public Works and Housing Main BuildingDomenico Adi Nugroho, Hitapriya Suprayitno, Tri Joko Wahyu AdiEffect of Waste Tire Rubber on the Durability Behavior of Cement Composites: A ReviewIsyaka Abdulkadir, Bashar S. MohammedPreliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset ManagementRia Asih Soemitro, Hitapriya SuprayitnoComparing the Result of Infrastructure and Facility Demand Distribution Similarity Test Between Using Percentage Value and Real ValueHitapriya Suprayitno, Vita Ratnasari, Ria Asih Aryani SoemitroLearn Asset Management based on PTPN 9 Case – Preliminary Overview of the Institution, the Function, and the General Business AssetsSoedarmawan Soewardi, Hitapriya Suprayitno, Ria Asih Aryani Soemitro JIFAM, Vol.2, Issue 2, Sebtember 2020Preliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset Management Ria Asih Aryani Soemitro &Hitapriya SuprayitnoManagement Model of Mambal Irrigation Area in the Efforts to Develop Environment-Based Agro-tourismI Gusti Agung Putu Eryani, A.A. Sg. Dewi Rahadiani & Cok Agung YujanaBase Influence Factors for Community-Based Road Quality in Slum Settlement AreasMochammad Reyhan Firland, Hitapriya Suprayitno, Eko Budi Santoso & Tri Joko Wahyu AdiAreas Evaluation of Pump Capacity in Pancasila Pumping Station, Madiun City, East Java Novi Andriany Teguh, Umboro Lasminto, Anak Agung Ngurah Satria Damarnegara & Mohamad Bagus AnsoriPreliminary Research on Air Passenger Volume Variation in Kilimanjaro International Airport, TanzaniaFreddy David Chilongola, Hitapriya Suprayitno & DewantiAnalysis of Project Performance Criteria for Design and Build Contract Taurista Yuristanti, I Putu Artama Wiguna & Herry Budianto